Schools without measurements: towards a pedagogy of recognition (Revista Lusófona de Educação, 2018)
Since the OECD launched the Program for International Student Assessment (PISA) in 2000, education measurements have mainly been concerned with recording and issuing results in terms of school success or failure based on items aimed at measuring academic achievement. A major consequence of this obsession with quantifiable results, which stems from a sort of statistical monoculture, has been a shift of our attention away from the seminal fact that, indeed, educational disparities are directly linked to social inequalities. Besides, the application of accountability criteria within systems of education tends to hide the increasing deregulation of the former. Contrary to its seeming appearance, the school institution lacks clearly drawn goals and measurements. This is why, even certainly helped by rating scales but also far beyond them, we need to rethink education in terms of social justice and turn our attention from equal opportunities towards equal positions. From this analytic framework, a critical reinterpretation of the schooling process is suggested in order to approach it with the perspective of an educational policy of recognition that seeks a reconstruction of citizenship.Keywords: social inequalities; equal opportunities; equal positions; recognition; social justice